Evaluation of environmental impacts through the Conesa methodology generated by the artisan brick industry in the Populated Center of Cormis, Jauja - Reza Orellana, Heinz Aracely (2024)
The artisan production of bricks has been a factor for the emergence of environmental conflicts in our country. For this reason, the objective of the investigation intends to evaluate and describe the environmental impacts through the CONESA methodology with respect to the brick manufacturing process in the Cormis—Jauja Population Center, for which 21 brick kilns were located in the field and the area was delimited. study area by occupation area. As a starting point, the earth extraction and firing stages were identified as those that generate the greatest environmental impact in the production of artisanal bricks. Of which, 7 aspects and 18 environmental impacts were identified, 3 of which are of severe importance and the rest are moderate in such a way that the depletion of the soil resource and the alteration of air quality are of greater importance with an assessment of − 63 and − 51 respectively for each stage, evidenced in the field. In conclusion, the two stages present a negative environmental impact in terms of the depletion of resources and the alteration of the quality of the environment and positive in the socioeconomic incidence of the artisans since they depend on the production and commercialization of the bricks to obtain economic income for their homes, in addition to the fact that the investigation will be based on subsequent studies in the study area. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.